Investigating the effects of particle shape on normal compression and overconsolidation using DEM - de Bono, John P.; McDowell, Glenn R. (Springer Verlag, 2016)
Discrete element modelling of normal compression has been simulated on a sample of breakable two-ball clumps and compared to that of spheres. In both cases the size effect on strength is assumed to be that of real silica sand. The slopes of the normal compression lines are compared and found to be consistent with the proposed equation of the normal compression line. The values of the coefficient of earth pressure at rest K0,nc are also compared and related to the critical state fiction angles for the two materials. The breakable samples have then been unloaded to establish the stress ratios on unloading. At low overconsolidation ratios the values of K0 follow a well-established empirical relationship and realistic Poisson ratios are observed. On progressive unloading both samples head towards passive failure, and the values of the critical state lines in extension in q–p' space are found to be consistent with the critical state angles deduced from the values of K0 during normal compression. The paper highlights the important role of particle shape in governing the stress ratio during both normal compression and subsequent overconsolidation.